"We belong to nature": Communicating Mental Health in an Indigenous Context - Sørly, Rita; Mathisen, Vår; Kvernmo, Siv (Qualitative Social Work, 2020)
The approach to standardized services in Norwegian mental health care is tailored to the needs of the majority population, focusing on diagnoses and overshadows an approach that understands, values and emphasizes Sámi storytelling and everyday life. This study aims to contribute knowledge regarding the promotion of user involvement in mental health care from the perspectives of Sámi mental health care users. A narrative approach offers an opportunity to unravel an indigenous approach to mental health care and user involvement. People organize their storytelling according to culturally available narratives. This paper focuses on 9 Sámi men’s and women’s stories related to user involvement in mental health care services. Through a thematic analysis of personal stories, we emphasize how the participants make sense of their needs as patients in a culturally adapted mental health context and their experiences living in Sámi core areas. The following four themes are identified as prerequisites for user involvement in services: (1) the expectation of raising children to be independent, (2) the importance of accepting and recognizing the Sámi identity, (3) the need to live in close relations with nature and family, and 4) the right to be in the Sámi mode. Based on the results of our analysis, we find that user involvement among Sámi mental health care users is related to important Sámi values and norms within the culture and that treatment without these important values could adversely affect user involvement in mental health services.